Evaluation of phytohormones and hydrogen peroxide in the corn crop (Zea mays L.) - Juárez-Santillán, Luis Felipe; Bonilla-Cruz, Saúl; Reyes-Gómez, Juan Pablo; Martínez-Reséndiz, Georgina; Extocapan-Molina, Jocabel; Armenta-Barrios, Julio Alfonso (Renewable Energy, Biomass & Sustainability, 2021)
The use of environmentally friendly growth promoters and chemical agents in agricultural production is an important and favorable challenge, since it would reduce the use of agrochemicals and therefore less pollution for the field. The main objectives of this study were to make treatments on corn crops with auxins, gibberellins and hydrogen peroxide; as well as determining what the main positive or negative effects are. A factorial experiment design was carried out with five experiments which were: 1) auxins, 2) gibberellins, 3) Hydrogen peroxide (H2O2), 4) auxins-gibberellins and 5) control; the crop was corn, soil and plant samplings were made every 20 days, the variables analyzed in the plant were stem diameter, stem size, number of leaves and root size; the soil was analyzed for nitrites, nitrates, pH, EC and Eh; a statistical analysis was performed with these (ANOVA and Tukey’s test). The five experiments were carried out and according to the results obtained, it can be said that the best treatments are those in which H2O2 and auxins were used, since these were in which the crop presented the highest values ​​of the variables analyzed in the plant. These results suggest that in subsequent studies experiments using phytohormones and H2O2 together.